Filtrodynamics: Time Dependent Trans‐Filter Pressure Signals for Early Detection and Monitoring of Particulates During Chemical Processing. Issue 3 (16th September 2013) - Brusamarello, Claiton; Drenski, Michael F.; Isakov, Artem; Reed, Wayne F.
Abstract In many chemical manufacturing processes particulates often appear in addition to the desired products. Frequently, these particulates are undesirable and ubiquitous in macromolecular reactors that produce and process both synthetic and natural macromolecules. In some cases, however, particulates are necessary, such as bacteria in a biotechnology reactor. This work presents 'filtrodynamics', a means for early detection and monitoring of particulates in chemical processes. Time‐dependent pressure signals across filters yield information on particulate populations. Moreover, a characteristic loading model has been proposed that self‐consistently interlinks the particle concentration, flow rates, and filter properties via a characteristic loading parameter Lc. Filtrodynamics may yield a low cost alternative to delicate and difficult to maintain online optical sensors.<inline-graphic xlink:href="ark:/27927/pgg4sxtbj93" content-type="mren201300152-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />